Patients' satisfaction toward services at emergency department in Hospital Universiti Sains Malaysia, Kelantan - Nor, Ahmad Ramadan Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Introduction: Emergency Departments is crucial and play an important role for public health. A cross sectional study was conducted to identify patient's satisfaction toward services at Emergency Department (ED) in Hospital USM, Kelantan. The objective of this study was to determine association between the score of satisfaction and socio-demographic, patient's age, gender, level of education, and waiting time. Method: A self-administered questionnaire was used to collect the data using questionnaires derived from the Visit-Specific Satisfaction Questionnaires included 14 questions based on a Likert scale. Data collection was done from December 2012 until March 2013. The subjects were selected using a non-probability sampling. Descriptive statistics were used throughout data analysis in a number of ways using SPSS version 20. Results: Fifty subjects were involved in this study. Majority of the subjects, 44 (88%) have high satisfaction with the services from ED Hospital USM and the rest 6 (12%) have moderate satisfaction. At the 5% significant level, the Ho is rejected if p<0.05. Using Spearman correlation test, there is a poor correlation (r= 0.183) comparison of mean between score of satisfaction and age. The finding showed that there is no significant association between score of satisfaction and age (p=0.203). For gender, using Mann Whitney test there is no significant association between score of satisfaction and gender (p=0.466). For level of education, using Kruskall Wallis test, there is no significant association between score of satisfaction and level of education (p= 0.287). The relationship between waiting time and score of satisfaction was investigated using Kruskall Wallis test. The result shows that p value is 0.00 I and z statistics is 18.325. So, there is a significant association between the score of satisfaction and waiting time. Conclusion: The study findings indicated that majority patient have good satisfactions with services at ED Hospital USM. However, efforts should focus on shortening waiting time. There still have room for improvement to increase patient's satisfaction in the future.